Nanostructured Borate Halides for Optical Second Harmonic Generation at Surfaces - Tan, Deming; Kirbus, Benjamin; Eng, Lukas M.; Ruck, Michael (European Journal of Inorganic Chemistry, 2020)
Optical second harmonic generation (SHG) at surfaces and interfaces is an exciting new technique. In order to achieve high surface specificity and sensitivity of the SHG technique, smaller particles of SHG materials are highly desired. Borate halides are regarded as a great source of SHG materials because of their outstanding nonlinear optical properties. Phase-pure nanostructured samples of three borate halides of the type A2B5O9X were synthesized at low temperature in task-specific ionic liquids (IL). Optimized reactions of acetates A(OAc)2 (A = Sr, Ba) and boric acid B(OH)3 with the mixed IL [P66614]X (X = Cl, Br) and LiNTf2 led to nano-rods of Sr2B5O9Cl, nano-needles of Sr2B5O9Br, and nano-sheets of Ba2B5O9Cl. The reaction route presented here might trigger the synthesis of other borate compounds. Efficient second-order nonlinear conversion by the nanostructured borate halides was confirmed using confocal SHG microscopy.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Borate halides; Ionothermal synthesis; Low temperature synthesis; Nanoparticles; Nonlinear optics